2007
DOI: 10.1007/s00586-006-0292-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of bilateral posterior dynamic and rigid fixation devices on the loads in the lumbar spine: a finite element analysis

Abstract: A bilateral dynamic stabilization device is assumed to alter favorable the movement and load transmission of a spinal segment without the intention of fusion of that segment. Little is known about the effect of a posterior dynamic fixation device on the mechanical behavior of the lumbar spine. Muscle forces were disregarded in the few biomechanical studies published. The aim of this study was to determine how the spinal loads are affected by a bilateral posterior dynamic implant compared to a rigid fixator whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
102
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(117 citation statements)
references
References 45 publications
(44 reference statements)
13
102
0
2
Order By: Relevance
“…The values were always below the magnitude of the intact spine for the three cord pretension cases under extension; however, the FCF was 22.6% higher than the intact spine for the case of 300-N cord pretension under torsion. These results indicate that Dynesys can alleviate facet loading on the implanted level under extension, and they follow a similar trend to the results presented by Rohlmann [11]. Although FCF was noticeably increased at the adjacent levels, it remains much lower than the values of the fusion model (?169% under extension; ?28.9% under torsion) [20].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The values were always below the magnitude of the intact spine for the three cord pretension cases under extension; however, the FCF was 22.6% higher than the intact spine for the case of 300-N cord pretension under torsion. These results indicate that Dynesys can alleviate facet loading on the implanted level under extension, and they follow a similar trend to the results presented by Rohlmann [11]. Although FCF was noticeably increased at the adjacent levels, it remains much lower than the values of the fusion model (?169% under extension; ?28.9% under torsion) [20].…”
Section: Discussionsupporting
confidence: 86%
“…This FE analysis showed that the insertion of Dynesys reduced the ROM of the implanted level in terms of flexion and lateral bending, but less so in extension. The results are in good agreement with most previous biomechanical studies in which the Dynesys reduced the ROM below the magnitude of the intact spine for the implanted level under flexion and lateral bending [8,9,11,13]. For the adjacent levels, the present study revealed that the ROM increased by at least 22.4% in flexion and 15.6% in lateral bending; these trends conflict with the findings of some in vitro tests under the load control method [9,21].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Indeed, for this reason, dynamic stabilization could provide a reduction of the negative effect of fusion on the adjacent spinal segments and on the global functioning of the spine [6]. Up to now, promising clinical results have been described using this technique [7][8][9][10][11][12][13], but still not definitive. Also, the longterm effects of dynamic stabilization are still under discussion, with a specific focus on the remodeling of the disc cartilage matrix, both at the implanted and at the adjacent levels, caused by the spinal biomechanics which is modified by the implanted device.…”
Section: Introductionmentioning
confidence: 99%
“…Stiffness or hybrid protocols, rather than flexibility protocols, must be used to study the effects of surgical interventions on the biomechanics of the adjacent (non-operated) spinal levels [28,40]. With these methods, segmental kinematics are evaluated for the intact nonfusion, fusion, and TDR situations at an identical spinal posture [14,26,27,29,36,40,41]. However, some of the studies that have been performed to study TDR's adjacent to fusions [10,25,34] did not apply hybrid testing methods [10,34], or applied bending using an offset shear force that resulted in combined bending and shear loading [25].…”
Section: Introductionmentioning
confidence: 99%